Handbook of cellulosic ethanol - Amarasekara, Ananda S. (Beverly, Mass. : Scrivener Publishing, 2014)
'This book gives the background, scientific theory, and recent research progress in producing cellulosic ethanol via different routes, as well as future directions, covering all aspects of cellulosic ethanol'--
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed February 19, 2014).
Keywords: Cellulosic ethanol; TECHNOLOGY & ENGINEERING -- Power Resources -- Fossil Fuels; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Cellulosic ethanol; Electronic books